2008
DOI: 10.1080/10691310802258232
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Library Instruction to Undergraduates: Incorporating Online Tutorials into the Curriculum

Abstract: Librarians can replace or supplement traditional in-class instruction with course-specific online tutorials. The literature demonstrates how tutorials customized for specific courses are more beneficial than tutorials on basic research skills. Many authors discuss creating online tutorials but do not design one devoted to a specific course. With increasing demand for instruction services, online tutorials can ease staffing concerns prevalent at many libraries and otherwise enhance the quality of instruction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Online tutorials, whether stand-alone, course-specific or assignment-specific are becoming increasingly popular because of workload constraints of academic information literacy librarians (Gynn and Miree, 2012;Armstrong and Georgas, 2006;Ganster and Walsh, 2008;Dewald, 1999). One major benefit of online tutorials is that they expand the reach of information literacy beyond what a librarian can do in-person.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Online tutorials, whether stand-alone, course-specific or assignment-specific are becoming increasingly popular because of workload constraints of academic information literacy librarians (Gynn and Miree, 2012;Armstrong and Georgas, 2006;Ganster and Walsh, 2008;Dewald, 1999). One major benefit of online tutorials is that they expand the reach of information literacy beyond what a librarian can do in-person.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another area for future study is in pairing the library's online instructional resources with in-person, librarian-user interactions. From the outset, Dewald (1999) asserted that online library instruction should work in tandem with in-class instruction; Ganster and Walsh (2008) found that many students still prefer face-to-face NLW 115,3/4 library learning interaction to online instruction. So whether this means teaching the more mechanical skills via online tutorials while addressing conceptual skills in face-to-face learning interactions (Baker, 2006), or considering more broadly how to activate students' prior knowledge and adapt to learning needs (Somoza-Fernandez and Abadal, 2009), how online tutorials are used to connect students to librarians and library information is an essential consideration going forward.…”
Section: Future Directionsmentioning
confidence: 99%
“…As technology learning options increase in scope and diversity, embedding this feedback becomes increasingly doable (Germain and Bobish, 2003), and tutorials with interactivity between learner and instructor are more highly rated by neutral professional library groups (Koh and Herring, 2007), and so increasing this interaction is important in effective tutorial design. Including contact mechanisms is particularly important because not all students desire to begin their information-seeking process with standalone online resources (Bowles-Terry et al, 2010); by providing a means to contact someone or seek additional help via chat, phone, email, or face-to-face contact, the online library tutorial works as a supplementary, rather than supplanting, resource to face-to-face interaction (Ganster and Walsh, 2008). The communication generated from these online points of help can illustrate where additional online library tutorials are needed and can respond to expressed student needs (Kimok and Heller-Ross, 2008).…”
mentioning
confidence: 99%
“…DaCosta Weetman and Jones (2007) successfully created an information literacy tutorial at De Montfort University in the UK using a 2003 Blackboard release, and also used Blackboard to gather assessment and reporting, but did not describe the process of using Blackboard as tool to achieve both. Ganster and Walsh (2008, p. 322) also explored the posting of an information literacy tutorial to Blackboard, but did not illustrate their methods in which they captured assessment from tutorial pre and post test data or produced reports.…”
Section: Literature Reviewmentioning
confidence: 99%